A Review on Literature as a part of Modern Culture - Bhavani Sushma Garlapati, (AG Volumes, 2022)
Literature is clear to see as having a wide range of subject matter that touches on all aspects of life. People from diverse social, political, cultural, economic, and intellectual backgrounds may have varied perspectives on the same literary work and the degree to which it is infused in their minds. It's hard to overstate the power of literature's energizing components. That needs to be grabbed in the right way. Hence, the major purpose of this research is to assess briefly the literature and its effect on human existence. Literature has a crucial role to play in human development as a teaching tool. Literature has a moral message, whether it is explicitly stated or implicit. There are several instances from various genres. Literature, therefore, is a potent educational tool. Philosophical thinking is regarded as the oldest kind of creative contemplation. Written literature, oral literature, scientific literature, and technical literature are all examples of literary genres. It serves a variety of purposes at various levels. Literature and society are intertwined in many ways. Writing is shaped by life, and life reflects any society's true pattern in literature. So it has been shown that literature has a significant impact on people's lives throughout time. Literature has a profound impact on our lives, educating us about a wide range of topics. Empathy and a fresh view of one's own and others' lives are sparked by stories, in particular.